Effect of soil bacteria on hyphal growth of the arbuscular mycorrhizal fungus Glomus claroideum - Gryndler, M; Hrselová, H; Stríteská, D (Folia microbiologica, 2000)
The effect of 46 bacterial strains isolated from tilled and non-tilled soils collected at 3 localities on the growth of intraradical hyphae of the arbuscular mycorrhizal (AM) fungus Glomus claroideum was demonstrated. A larger number of stimulatory bacterial isolates was obtained from tilled soils, but the bacteria showing the strongest stimulation of hyphal growth were isolated from a soil that had not been cultivated. Isolates obtained from hyphae of AM fungi showed no substantial stimulatory effects, but produced more uniform effects on hyphal growth than the isolates of bacteria obtained from soil. Bacterial cenoses present in 3 different soils differ significantly in their effects on AM fungi.
Keywords: zemědělství; Agriculture; Fungi; půdní mikrobiologie; Bacteria; jedlé rostliny; houby; Bacterial Physiological Phenomena; Plants, Edible; Soil Microbiology; fyziologie bakterií